Electrochemical and AFM study of corrosion inhibition with respect to application method - Otmačić Ćurković, Helena (Array, 2009)
Summary: The aim of this work was to investigate how the efficiency of a corrosion inhibitor and the mechanism of its inhibiting action depend on the inhibitor application method. Studies were performed on copper in 0.5 M NaCl solution for two imidazole derivatives. Studied compounds were either added to the corrosive solution or the inhibitor film was formed prior to immersion in the corrosive solution. The investigations were conducted by means of electrochemical methods and atomic force microscopy. The results obtained indicate that the method of inhibitor application may determine the mechanism of inhibition and the efficiency of an inhibitor. When the inhibitors were adsorbed on the metal surface from the organic solvent, they acted primarily as cathodic corrosion inhibitors. On the other hand, when they were added to the aqueous solution, both anodic and cathodic reaction rates slowed down. AFM studies have also confirmed changes in the inhibition mechanism due to the application method. All experimental methods have confirmed that the studied imidazole compounds can control the corrosion processes more efficiently when they are dissolved in a chloride solution than when used in nanolayers